Kesesuaian Isi Buku Ajar BIPA â€œSahabatku Indonesiaâ€ untuk Penutur Bahasa Inggris Level 1 (Conformity of BIPA Textbook Contents â€œSahabatku Indonesiaâ€ for Level 1 English Speakers) - Kurniawan Kurniawan; Royan Nur Fahmi; Indrya Mulyaningsih (Jurusan Tadris Bahasa Indonesia, 2022)
Through the Indonesian Language for Foreign Speakers (BIPA) program, various people in the world are interested in learning Indonesian. This study aims to describe the suitability of the BIPA textbook entitled